The emergence and decline of ethnic minorities in Baltic borderlands - Lundén, Thomas U. (Creativity Studies, 2012)
The purpose of the paper is to discuss the emergence and decline of national and / or ethnic minorities in the borderlands around the Baltic Sea. The socio-political development of ethnic groups is seen as a result of different influencing factors: The territorial history, the change of state borders and population groups plus relations beyond the state territory. Several criteria were found to determine the development, non-development or decay of national allegiance. The change, establishment or eradication of state boundaries, the ethnic cleansing of areas, mostly for the sake of “nation-state” homogeneity, the assimilation of a potential ethnic group into the majority population, and the non-emergence of a national movement. Etninių mažumų iškilimas ir išnykimas baltiškuosiuose paribiuoseSantrauka. Straipsnio tikslas – aptarti tautinių ir (arba) etninių mažumų Baltijos jūros paribiuose iškilimą ir išnykimą. Sociopolitinė etninių grupių raida suprantama kaip skirtingų įtakos turinčių veiksnių rezultatas: teritorinė istorija, valstybės sienų kaita ir populiacijos grupės, taip pat santykiai už valstybės teritorijos. Buvo pasirinkti skirtingi kriterijai tautinės ištikimybės raidai, ne-raidai ar jos žlugimui apibrėžti. Valstybės sienų permaina, įsteigimas ar sunaikinimas, etninis plotų valymas daugiausia dėl „tautos-valstybės“ homogeniškumo, potencialios etninės grupės asimiliavimasis į didžiąją populiaciją ir tautinio judėjimo neiškilimas.Reikšminiai žodžiai: Baltijos jūros regionas, paribys, etniškumas, kalba, mažuma, populiacija, teritorija.